AI & Events Management - Daniel MOISE; Maria Loredana POPESCU; Amelia DIACONU; Sorin BURLACU; Maria Alexandra SARBU (Communications of International Proceedings, 2021)
Artificial Intelligence (AI) is already used in our daily lives and will be used more and more in the near future. AI development is done in both ways, intensively and extensively. The use of AI in projecting, organizing and deployment is something that will not be just a “cool thing” to use, but a “must have” in order to have not just “better”, but “smarter” and safer events. In this article, we are going to study the perception of the use of AI in organizing events from the perspective of the direct audience acceptance. Most of the respondents mentioned if the use of AI by the organizing committee could enhance and ease their experience while taking part in different events is a plus. At the same time, issues like the reduction of use of human labor and the difficulties experienced when interacting with an AI software and AI apps are seen as “black or white” decision makers.
Keywords: Artificial Intelligence (AI); smarter events; safer events; sustainable events.